The Impact Of Pakserv On Customer Satisfaction And Loyalty: Study Case Grabfood Indonesia - Aningsih Wulandari, Yahyu; Amir, Fakhrurrazi; Iqbal Fajri, Muhammad (Journal of World Science, 2022)
Every business needs an excellent service quality to make customer satisfied and loyal. However, the terms of satisfaction and loyal still become the problems that should be tackled like GrabFood in Banda Aceh which should cope the food service delivery delay to the customer. This research uses PAKSERV model to give the solution for improving the service quality, the population in this research is the users of grabfood Banda Aceh and the sample 204 users with purposive sampling. This research uses SEM-PLS with the help of AMOS and SPSS software which found that Tangibility has a significant and positive impact on customer satisfaction along with other variables such as Assurance, Personalization, Sincerity, and Formality. On the other hand, Reliability in this model has not a significant impact to the customer satisfaction even-though it has a positive impact. Thus, it could be interpreted that, GrabFood Banda Aceh should pay more attention to the Tangibility, Assurance, Personalization, Sincerity and Satisfaction.